2000
DOI: 10.1007/s004280000190
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic sarcomatoid carcinoma (carcinosarcoma) of the renal pelvis with heterologous chondrogenic differentiation

Abstract: A case of a man with biphasic sarcomatoid carcinoma of the right kidney with chondrosarcomatous foci and with invasion of the pelvic mucosa and submucosa into the peripelvic adipose tissue is presented. In situ carcinoma of the urothelium of the right renal pelvis and proximal ureter was also noted. Comments on the nomenclature of malignant tumours with apparently mixed carcinomatous and sarcomatous phenotypes and a hypothesis on the histogenesis of these tumours are presented. Cytokeratin and p53 protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…A similar case with a protracted course was published by others [13]. In the majority of cases, however, the prognosis is poor and patients seldom survive longer than 3 years [10,19,24].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A similar case with a protracted course was published by others [13]. In the majority of cases, however, the prognosis is poor and patients seldom survive longer than 3 years [10,19,24].…”
Section: Discussionsupporting
confidence: 70%
“…A few cases were located in the renal pelvis or proximal ureter [14,17,24]. Tobacco smoking and irradiation of the genital tract in gynecological patients have been considered risk factors for the development of SC [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Immunohistochemical studies of the spindle cell component have demonstrated frequent expression of cytokeratin (CK), at least focally, as well as the expression of other epithelial markers, such as epithelial membrane antigen (EMA), but less consistently than CK. 15 Coexpression of vimentin is common, with muscle-specific actin infrequently expressed. 13,14 Immunohistochemical studies demonstrating biphasic differentiation (e.g., examinations of cytokeratin and vimentin expression revealed epithelial and mesenchymal differentiation, respectively) were also mandatory in the current diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the "References," Chiu et al cited only nine papers regarding carcinosarcoma of the renal pelvis. [2][3][4][5][6][7][8][9][10] Other reports of carcinosarcoma of the renal pelvis have not been reviewed by Chiu et al [11][12][13][14] According to Kobayashi et al's review, 15 a total of 19 cases of carcinosarcoma or sarcomatoid carcinoma of the renal pelvis have been reported up until 1994. Eleven cases were reported as "true" carcinosarcoma and eight as sarcomatoid carcinoma.…”
mentioning
confidence: 99%